Colletotrichum higginsianum Mitogen-Activated Protein Kinase ChMK1: Role in Growth, Cell Wall Integrity, Colony Melanization, and Pathogenicity - Wei, Wei; Xiong, Ying; Zhu, Wenjun; Wang, Nancong; Yang, Guogen; Peng, Fang (Frontiers in Microbiology, 2016)
Colletotrichum higginsianum is an economically important pathogen that causes anthracnose disease in a wide range of cruciferous crops. To facilitate the efficient control of anthracnose disease, it will be important to understand the mechanism by which the cruciferous crops and C. higginsianum interact. A key step in understanding this interaction is characterizing the mitogen-activated protein kinases (MAPK) signaling pathway of C. higginsianum. MAPK plays important roles in diverse physiological processes of multiple pathogens. In this study, a Fus3/Kss1-related MAPK gene, ChMK1, from C. higginsianum was analyzed. The results showed that the Fus3/Kss1-related MAPK ChMK1 plays a significant role in cell wall integrity. Targeted deletion of ChMK1 resulted in a hypersensitivity to cell wall inhibitors, reduced conidiation and albinistic colonies. Further, the deletion mutant was also unable to form melanized appressorium, a specialized infection structure that is necessary for successful infection. Therefore, the deletion mutant loses pathogenicity on A. thaliana leaves, demonstrating that ChMK1 plays an essential role in the early infection step. In addition, the ChMK1 deletion mutant showed an attenuated growth rate that is different from that of its homologue in C. lagenarium, indicating the diverse roles that Fus3/Kss1-related MAPKs plays in phytopathogenic fungi. Furthermore, the expression level of three melanin synthesis associated genes were clearly decreased in the albinistic ChMK1 mutant compared to that of the wild type strain, suggesting that ChMK1 is also required for colony melanization in C. higginsianum.